Blue Tits "Cyanistes caeruleus" and great tits "Parus major" as urban habitat breeders - Bańdura, Jerzy; Bańdura, Mirosława (Zielona Góra: University of Zielona Góra, Faculty of Biological Sciences)
The Great Tit "Parus major" and the Blue Tit "Cyanistes caeruleus" are the only Western Palearctic Parids that maintain numerous urban populations as well as forest populations. Because of their evolutionary history both these species are best adapted to different types of deciduous and mixed forests. Ecological conditions in cities are different from those dominating in forests, especially in such aspects as: habitat fragmentation, tree species composition, microclimate, human activity, predators and food conditions.
Keywords: Parus; Cyanistes; urbanization; breeding; trophic conditions; mortality